Upgrade recycling of cast iron scrap chips towards β-FeSi2 thermoelectric materials - Nor Hairin, Assayidatul Laila; Nanko, Makoto; Takeda, Masatoshi (MDPI AG, 2014)
The upgrade recycling of cast-iron scrap chips towards β-FeSi2 thermoelectric materials is proposed as an eco-friendly and cost-effective production process. By using scrap waste from the machining process of cast-iron components, the material cost to fabricate β-FeSi2 is reduced and the industrial waste is recycled. In this study, β-FeSi2 specimens obtained from cast iron scrap chips were prepared both in the undoped form and doped with Al and Co elements. The maximum figure of merit (ZT) indicated a thermoelectric performance of approximately 70% in p-type samples and nearly 90% in n-type samples compared to β-FeSi2 prepared from pure Fe and other published studies. The use of cast iron scrap chips to produce β-FeSi2 shows promise as an eco-friendly and cost-effective production process for thermoelectric materials.